Preclinical study of the topical anti-inflammatory activity of Cyperus rotundus L. extract (Cyperaceae) in models of skin inflammation. (23rd May 2020) - Rocha, Fernanda Grillo; Brandenburg, Margareth de Mello; Pawloski, Priscila Lúcia; Soley, Bruna da Silva; Costa, Simone Castagna Angelim; Meinerz, Cristiane Claudia; Baretta, Irinéia Paulina; Otuki, Michel Fleith; Cabrini, Daniela Almeida
Abstract: Ethnopharmacological relevance: Cyperus rotundus L. ( Cyperaceae) is considered one of the most widely distributed plant species in the world, especially in tropical and subtropical regions. In addition, it is commonly used in India, China and Japan in traditional medicine to treat different diseases, including dermatitis and other skin disorders. Aim of the study: To investigate the topical anti-inflammatory activity of C. rotundus rhizome ethanolic extract in models of acute and chronic dermatitis. Materials and methods: Phytochemical analysis was carried out using High-performance liquid chromatography-ultraviolet detection (HPLC/UV) to determine the presence of quercetin and chlorogenic acid in C. rotundus extract. Topical anti-inflammmatory effects of C. rotundus extract were evaluated on arachidonic acid (AA) and 12-O-tetradecanoylphorbol-13-acetate (TPA)-induced skin inflammation in mice. Skin biopsies were collected and submitted to histological and enzymatic analysis to evaluate the C. rotundus effect in leukocyte migration into inflamed tissue. Antiproliferative activity of C. rotundus was confirmed by PCNA immunostained cell analysis. Systemic and possible adverse effects of topical treatment with C. rotundus were evaluated by the skin atrophy and same organ weights. In addition, the glucocorticoid receptor (GR) antagonist mifepristone was used to investigate possible GR-mediated mechanisms of action. Results: The phytochemical analysis show that C. rotundus ethanol extract contains 45 μg/g of chlorogenic acid. Topical treatment with C. rotundus extract reduced ear edema and cellular infiltrate in acute and chronic skin inflammation models. Moreover, mice topically treated with C. rotundus exhibited decrease in TPA-induced keratinocyte hyperproliferation. Relevantly, topical treatment with C. rotundus did not caused skin atrophy or changes in lymphoid organ weight. The anti-inflammatory effect of C. rotundus was not influenced by the GR antagonist. Conclusion: The results here demonstrate for the first time the topical anti-inflammatory and antiproliferative efficacy of C. rotundus extract, suggesting that the extract could be a potential new therapeutic tool for the treatment of inflammatory skin disorders. Graphical abstract: Image 1